Analyzing the Relationship Between Management Efficiency, Capital Structure, and Firms' Performance in a Turbulent Environment : Evidence from India - Khanna, Sakshi; Srivastava, Amit; Medury, Yajulu (Indian Journal of Research in Capital Markets, 2015)
The financing policy plays an important role in attaining strong economic fundamentals for the firms in the long run. For obtaining a unified financing policy, it is important to study the linkage between the firms' financing policy and their performance in different phases of the cycle. This study analyzed the effect of the 2008 business cycle on the performance of Indian firms with respect to management efficiency in terms of their choice of capital during the period of recession (2008-09). It is a panel data study and the sample consists of the firms listed on BSE for the time period from 1997-2013. The results showed that there is a difference in the performance of the firms dependingÂ upon their choice of capital. It also discussed the possible actions the managers could undertake while raising finances in order to maximize the value of the firms.